Metallic love - Lee, Tanith ([Pymble, N.S.W.] : Voyager, 2013)
twelve years have passed since the end of the Silver Metal Lover. Silver - the robot with a soul whom Jane had fallen in love with - has been melted down, and Jane has moved on. Loren is a slum child, abandoned by her mother and raised by the religious cult, the Apocalytes. One day, she discovers an illegal copy of Jane's book - the story of Jane and Silver's love that has become a cult classic - and it changes her life. Motivated by her desire to taste the life that Jane and Silver had, she runs away to the City. But Loren is not like the privileged and romantic Jane. Hard-edged and realistic, she sees the world through the eyes of the underclass. Loren's cynicism is shattered when a new company brings back the very robots that were destroyed twelve years before - only better, faster and more superhuman; if the original robots had been perfection, their descendants are now like gods. then Loren meets the new Silver, who is nothing like the original, and she realises that maybe everything in Jane's book is nothing but a pack of lies. As beautifully and lyrically written as its predecessor, Metallic Love is both an improbable love story and a novel about illusions.
Imprint: Voyager.
Online resource; title from cover on title info screen (OverDrive, viewed September 17, 2015)
Keywords: Androids -- Fiction; Orphans -- Fiction; Androids; Fiction - Science Fiction - General; Orphans; Science fiction; Australian; Electronic books; Fiction